Intravascular Lithotripsy for Treatment of Calcified Lesions During Carotid Artery Stenting. (February 2021) - Giannopoulos, Stefanos; Speziale, Francesco; Vadalà, Giuseppe; Soukas, Peter; Kuhn, Brian A.; Stoltz, Chad L.; Foteh, Mazin I.; Mena-Hurtado, Carlos; Armstrong, Ehrin J.
Purpose: To report the use of intravascular lithotripsy (IVL) in the treatment of calcified carotid artery lesions. Materials and Methods: The records of 21 high-surgical-risk patients (mean age 75.1±8.1 years; 17 men) who were treated at 8 centers for carotid artery stenosis ≥70% were retrospectively reviewed. Twelve patients had a history of cerebrovascular disease. All patients had heavily calcified carotid artery lesions: 19 de novo and 2 in-stent restenoses (ISR). The mean baseline stenosis was 82.3%±9.7%. IVL was utilized at the discretion of the operator, followed by balloon angioplasty. Embolic protection devices were used in all cases. Results: In 19 patients, IVL was followed by stent implantation; the 2 ISR lesions were dilated only. The mean IVL balloon diameter was 4.64±1.13 mm, and the mean number of IVL pulses applied was 67.2±61.4 (range 10–180). All procedures were technically successful (<30% residual stenosis). No patients developed symptomatic bradycardia or hypotension due to IVL, and there were no adverse events associated with IVL delivery. All patients were discharged on dual antiplatelet therapy. Seventeen days after the procedure, 1 patient experienced an ischemic stroke that was deemed due to aortic arch manipulation during transfemoral access. Carotid duplex ultrasound examination identified significant restenosis (>70%) in 1 asymptomatic patient at 12 months after the index procedure. No patients required reintervention during a median follow-up of 6 months (range 1–12). Conclusion: This preliminary experience demonstrates that IVL can be a safe and effective approach for the management of severely calcified carotid lesions. Further research is warranted to determine the longer-term safety and efficacy of IVL for dilation of calcified carotid artery lesions as an adjunct to carotid artery stenting.